Expression of Semaphorin 3F and Its Receptors in Epithelial Ovarian Cancer, Fallopian Tubes, and Secondary Müllerian Tissues - Christina D. Drenberg; Sandra Livingston; Ren Chen; Patricia A. Kruk; Santo V. Nicosia (Obstetrics and Gynecology International)
While semaphorins and their receptors appear to play a role in tumor carcinogenesis, little is known about the role of semaphorin 3F (S3F) in epithelial ovarian cancer (EOC) development. Therefore, we sought to determine the clinical relationship between S3F and its receptors, neuropilin-2 (NP-2) and neuropilin-1 (NP-1) with EOC progression. We analyzed the immunohistological expression of S3F, NP-2, and NP-1 in clinical specimens of normal ovaries (N), benign cystadenomas (Cy), well-differentiated adenocarcinomas (WD), poorly-differentiated adenocarcinomas (PD), inclusion cysts (IC), paraovarian cysts (PC), and fallopian tubes (FT). Tissue sections were evaluated for staining intensity and percentage of immunoreactive epithelia. We found that expression of S3F and NP-2 decreased while NP-1 expression increased with EOC progression. Interestingly, we also found elevated expression of S3F, NP-2, and NP-1 in epithelia of ICs, PCs, and FT. Our findings indicate that loss or deregulation of semaphorin signaling may play an important role in EOC development.